Money Politics and Electoral Clientelism in the 2024 Legislative Election: A Case Study in Malang City - Favian, Dhien (Universitas Brawijaya, 2026)
This research aims to uncover the transformation of money politics in the 2024 Legislative Election in Malang City. Using the framework of electoral clientelism, this research examines how candidates adapt to tight competition through organized material exchange strategies. The method used is a descriptive qualitative case study approach in two villages in Malang City. Primary data were collected through field observations, participatory monitoring by Malang Corruption Watch (MCW), and in-depth interviews with key informants. The research suggests that money politics in Malang City has evolved from conventional vote buying to